Progress and Challenges Toward Generation and Maintenance of Long-Lived Memory T Lymphocyte Responses During COVID-19 - Kumar, Swatantra; Saxena, Shailendra K.; Maurya, Vimal K.; Tripathi, Anil K. (Frontiers in Immunology, 2022)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) causing Coronavirus disease 2019 (COVID-19) pandemic is the serious global threat until we identify the effective preventive and therapeutic strategies. SARS-CoV-2 infection is characterized by various immunopathological consequences including lymphocyte activation and dysfunction, lymphopenia, cytokine storm, increased level of neutrophils, depletion and exhaustion of lymphocytes. Considering the low level of antibody mediated protection during coronavirus infection, understanding the role of T cell for long term protection is decisive. Both CD4+ and CD8+ T cell response is imperative for cell mediated immune response during COVID-19. However, the level of CD8+ T cell response reduced to almost half as compared to CD4+ after six months of infection. The long-term protection is mediated via generation of immunological memory response during COVID-19. The presence of memory CD4+ T cells in all the severely infected and recovered individuals shows the memory response is predominated by CD4+ T cells. Prominently, the antigen-specific CD4+ and CD8+ T cells are prominently observed in day 0 to day 28 in COVID-19 vaccinated individuals. However, level of antigen-specific T memory cells in COVID-19 vaccinated individuals defines the long-term protection against forthcoming outbreaks of SARS-CoV-2.